RNA Sequencing Reveals Candidate Genes and Pathways Associated with Resistance to MDM2 Antagonist Idasanutlin in TP53 Wild-Type Chronic Lymphocytic Leukemia - Aptullahoglu, Erhan; Nakjang, Sirintra; Wallis, Jonathan P.; Marr, Helen; Marshall, Scott; Willmore, Elaine; Lunec, John (Biomedicines, 2024)
Chronic lymphocytic leukemia (CLL) is a genetically and clinically diverse hematological cancer affecting middle-aged and elderly individuals. Novel targeted therapy options are needed for patients who relapse following initial responses or who are intrinsically resistant to current treatments. There is a growing body of investigation currently underway on MDM2 inhibitors in clinical trials, reflecting the increasing interest in including these drugs in cancer treatment regimens. One of the developed compounds, idasanutlin (RG7388), has shown promise in early-stage clinical trials. It is a second-generation MDM2–p53-binding antagonist with enhanced potency, selectivity, and bioavailability. In addition to the TP53 status, which is an important determinant of the response, we have shown in our previous studies that the SF3B1 mutational status is also an independent predictive biomarker of the ex vivo CLL patient sample treatment response to RG7388. The objective of this study was to identify novel biomarkers associated with resistance to RG7388. Gene set enrichment analysis of differentially expressed genes (DEGs) between RG7388-sensitive and -resistant CLL samples showed that the increased p53 activity led to upregulation of pro-apoptosis pathway genes while DNA damage response pathway genes were additionally upregulated in resistant samples. Furthermore, differential expression of certain genes was detected, which could serve as the backbone for novel combination treatment approaches. This research provides preclinical data to guide the exploration of drug combination strategies with MDM2 inhibitors, leading to future clinical trials and associated biomarkers that may improve outcomes for CLL patients.